The Interpretive History of Di’s Meaning: The Misreading in Ming and Qing Dynasties and Uncovering of Modern Scholars - CUI, Liguo (Journal of Research for Christianity in China (JRCC), 2025)
“Di” is an important term in Chinese culture, and its interpretation of the supreme god and personality god has gone through the process of misreading, construction, concealing and uncovering. There are controversies between ancients and moderns, as well as between China and the West, which is a concentrated history of Chinese culture suffering since Ming and Qing Dynasties.The research on the meaning of “Di” is concentrated in the fields of philology and oracle bone script. At present, there is no comprehensive investigation of the value presupposition of the social general concept on this understanding, and the interference and influence caused by the cultural integration activities of western missionaries have not been pointed out. Based on the academic history, this article points out that the true interpretation of “Di” was influenced by Term Question in the late Ming dynasty and the early Qing Dynasty, so that the character of God in the Bible was equated with the meaning of “Di” in ancient Chinese cannon, which became a widely accepted concept in Chinese society, and influenced later historians' understanding of “Di” on oracle bones. Recently, different views have been put forward on the study of the meaning of “Di” in oracle bones, and the truth of the meaning of “Di” is gradually revealed.
Keywords: “Di”, Term Question, Supreme God, Personality God, Ancestor god